Enhancing ultra-early strength of sulphoaluminate cement-based materials by incorporating graphene oxide - Liu Yushi; Jia Minjie; Song Chengzhe; Lu Shuang; Wang Hui; Zhang Guanhua; Yang Yingzi (Nanotechnology Reviews, 2020)
In order to meet the increasing engineering requirements, the ultra-early strength of sulphoaluminate cement (SAC)-based materials need to be improved to achieve road repair, engineering rescue and other objectives. Graphene oxide (GO) of 0.04 wt% was incorporated into SAC mortar to prepare GO enhanced SAC mortar (GO-SAC). It was found that the compressive strength of GO-SAC was increased by 46.9% at the age of 6 hours, and the flexural strength of GO-SAC was increased by 121.4% at the age of 100 minutes, compared with the control SAC mortar. The mechanism analysis based on the characterization results derived from XRD, BET, in situ ATR-FTIR, hydration heat measurement, TG–DSC and SEM showed that, the addition of minute quantities of GO led to the formation and growth of ribbon-like AFt,which further resulted in the improvement of the ultra-early strength of GO-SAC. This work indicates that GO has great potential for practical application in the preparation of high-performance SAC-based materials with ultra-early strength.